2016
DOI: 10.18240/ijo.2016.01.25
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin can arrest the cone photoreceptor degeneration and act as a novel treatment for retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a group of heterogeneous inherited retinal diseases that is characterized by primary death rod photoreceptors and the secondary loss of cones. The degeneration of cones causes gradual constriction of visual fields, leaving the central islands that are eventually snuffed out. Studies indicate that the hyperoxia causes oxidative damage in the retina and contributes to the cone death of RP. Moreover, abundant reactive oxidative species (ROS) which are generated in cones may result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The beneficial effects of resveratrol and lutein are reproduced by Vaccinium myrtillus since it contains high amounts of antioxidant and anti-inflammatory polyphenols (anthocyanins and resveratrol) [ 49 , 217 , 218 , 219 ]. This is documented in various experimental models of retinal degeneration [ 217 , 218 , 219 ].…”
Section: Lutein Resveratrol and Vaccinium Myrtillus mentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of resveratrol and lutein are reproduced by Vaccinium myrtillus since it contains high amounts of antioxidant and anti-inflammatory polyphenols (anthocyanins and resveratrol) [ 49 , 217 , 218 , 219 ]. This is documented in various experimental models of retinal degeneration [ 217 , 218 , 219 ].…”
Section: Lutein Resveratrol and Vaccinium Myrtillus mentioning
confidence: 99%
“…Nonetheless, a deep knowledge of AMD pathogenic mechanisms is still lacking so far, which complicates the establishment or approval of effective treatment strategies. While the overactive angiogenesis and visual deficits occurring in wet AMD can be mitigated by anti-VEGF drugs, this is not the case for dry AMD [ 45 ] Recent evidence-based studies show that dietary phytochemicals such as lutein/zeaxanthin, resveratrol, and Vaccinium myrtillus may be beneficial in retinal diseases including AMD [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In general, these compounds have been claimed to interfere with the biology of disease by mitigating oxidative stress and inflammation, which play a critical role in the initiation and progression of AMD [ 47 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the disease-causing mutation resides within rod genes, it is the secondary loss of cones that leads to total blindness. The mechanism behind this is not fully understood, but it is known that oxidative stress is a key factor [6] , [7] , [8] , [41] , [60] . Gene therapy is a promising therapeutic approach for RP, however targeting the multitude of RP-related genes is complex and so ROS pathways provide viable indiscriminate therapeutic targets, where the aim is to retard retinal degeneration and preserve vision.…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins can exert different effects on vision health, as attested by many recent studies (reviewed in [ 74 ]): (i) they showed relaxing activities on ciliary smooth muscle, which is involved in the control of lens focus, in the production of aqueous humour and in the maintenance of ocular pressure, thus demonstrating possible therapeutic uses in the treatment of visual fatigue and important ocular disorders such as myopia and glaucoma; (ii) they stimulated the regeneration of rhodopsin, after being photo-bleached by light, a mechanism that is necessary to make this photoreceptor active to carry out again its function in the visual photo transduction process; (iii) being able to inhibit the elongation of axial and ocular lengths caused by wearing a negative lens in animal models, they could be useful in the prevention of myopia, a very common cause of impaired vision in young and adult people, due to a refractive error induced by the elongation or curvature of the eye shape; (iv) they improved dark adaptation and night vision by the enhanced generation of retinal pigments; and (v) they increased retinal blood circulation and could therefore be useful in preventing the early stages of diabetic retinopathy or glaucoma. The antioxidant and scavenging activities of anthocyanins could also affect the production of ROS inducing the apoptotic degeneration of the photoreceptor cells, which is responsible for the gradual constriction of the central visual field, leading to blindness in retinitis pigmentosa [ 75 , 76 ]. In this context, the extract of the Japan blue tomato was tested in vitro on murine photoreceptor cells and found to significantly reduce cone cell death by scavenging hydrogen peroxide [ 62 ].…”
Section: Anthocyanins From Purple Tomatoes and Human Healthmentioning
confidence: 99%